1933
DOI: 10.1172/jci100541
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Total Pulmonary Capacity and Its Sub-Divisions. Ii. Correlation With Physical and Radiological Measurements

Abstract: In a previous paper (5) we have presented the results of 50 determinations of pulmonary capacity made in an equal number of healthy males.It was demonstrated that the relative capacities (expressed in percentages of the total volume) fluctuated within narrow limits, but that there were wide variations in the absolute figures found for the total volume and its subdivisions. This fact makes rather difficult the recognition of moderate, and perhaps important, deviations in a given case, and also prevents a clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1933
1933
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 6 publications
2
25
0
Order By: Relevance
“…It was found that the normal values gathered from the literature were insufficient to afford an adequate basis for the detection of pathological alterations, and preliminary studies were consequently made in healthy subjects. The results of measurements made in fifty normal male subjects have been presented in previous papers (11), (12). The data show definite limits of variation for the relative values of some of the subdivisions of the total pulmonary capacity, as well as a definite correlation between the pulmonary capacity and combined physical and radiological measurements of the chest.…”
mentioning
confidence: 76%
“…It was found that the normal values gathered from the literature were insufficient to afford an adequate basis for the detection of pathological alterations, and preliminary studies were consequently made in healthy subjects. The results of measurements made in fifty normal male subjects have been presented in previous papers (11), (12). The data show definite limits of variation for the relative values of some of the subdivisions of the total pulmonary capacity, as well as a definite correlation between the pulmonary capacity and combined physical and radiological measurements of the chest.…”
mentioning
confidence: 76%
“…Measurements of the total pulmonary capacity and its subdivisions and their relation to anatomical findings in patients with chronic pulmonary diseases have been presented in previous communications (1) (2). The limits of variation in normal subjects, both male and female, and the method for the prediction of the normal capacity of a given subject have been described (1) (2) (3).…”
mentioning
confidence: 99%
“…The total pulmonary capacity and its sub-divisions were measured according to the methods used in this clinic (11,12).…”
Section: Methodsmentioning
confidence: 99%